(untitled) (Bangladesh Journal of Pharmacology, 2015)
A new series of N-substituted phthalimide derivatives were prepared by condensation of appropriate amount of n-amino tetrachlorophthalimide with respective aldehyde in glacial acetic acid. The structural investigation of the synthesized compounds was done by spectroscopic methods (UV-Vis., IR, 1H and 13C NMR) and elemental analysis. The antibacterial screening of these compounds was performed against Escherichia coli and Staphylococcus mutans. The synthesized compounds were evaluated for their antioxidant potential using 2,2-diphenyl-1-picrylhydrazyl (DPPH) as a scavenging agent. The interaction ability of most promising compounds (3a and 3b) with native calf thymus DNA (Ct-DNA) was also studied by means of UV-Vis., circular dichroism (CD), viscosity measurements and thermal studies. The intrinsic binding constants (Kb) of 3a and 3b with Ct-DNA obtained from UV-Vis. absorption studies were 8 × 104 and 1 × 105, respectively. Molecular docking of target compounds (3a and 3b) against DNA dodecamer d(CGCGAATTCGCG)2 has been carried out. The test compounds exhibited remarkable antibacterial, antioxidant and DNA binding activities.